2016
DOI: 10.18406/2316-1817v8n42016870
|View full text |Cite
|
Sign up to set email alerts
|

Análise do comportamento dos consumidores de feiras livres na microrregião de Formiga (MG)

Abstract: O objetivo do trabalho é compreender quais fatores são capazes de influenciar os consumidores em suas decisões de compra nas feiras livres. Nesse sentido, a unidade de observação da pesquisa foram as feiras livres dos municípios da microrregião de Formiga, estado de Minas Gerias, e a unidade de análise foram os consumidores dessas feiras livres. Os resultados apontaram para características comportamentais marcadas por variáveis que valorizam a qualidade de vida, economia de tempo, dinheiro e valores sociais co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
0
2
1
3
Order By: Relevance
“…The vast majority of consumers (65.49%) said they eventually attend the free fair, but only 22.12% attend every week. This frequency of going differs from that found in other studies (Costa, Andrade & Felipe, 2016;Lobo, Cavalcante, Albuquerque & Calheiros, 2020), since the products offered at the fair, such as vegetables, dairy products, and bread (Rockenbach et al, 2021) are perishable and consumed daily, making consumers tend to return to the place more often. In a study carried out at the free fair in Maceió -AL, the frequency of weekly visits was 64.7% and, of these, 94.2% state that the visit is due to the need for the products offered (Lobo et al, 2020).…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…The vast majority of consumers (65.49%) said they eventually attend the free fair, but only 22.12% attend every week. This frequency of going differs from that found in other studies (Costa, Andrade & Felipe, 2016;Lobo, Cavalcante, Albuquerque & Calheiros, 2020), since the products offered at the fair, such as vegetables, dairy products, and bread (Rockenbach et al, 2021) are perishable and consumed daily, making consumers tend to return to the place more often. In a study carried out at the free fair in Maceió -AL, the frequency of weekly visits was 64.7% and, of these, 94.2% state that the visit is due to the need for the products offered (Lobo et al, 2020).…”
Section: Resultscontrasting
confidence: 84%
“…In a study carried out at the free fair in Maceió -AL, the frequency of weekly visits was 64.7% and, of these, 94.2% state that the visit is due to the need for the products offered (Lobo et al, 2020). In a free fair in the municipality of Formiga -MG, Costa et al (2016) observed that 82.5% of the people interviewed attend the free fair every week, while 17.5% said they go only two or fewer times a month. The findings of the aforementioned authors reinforce the idea that the free fair is a space for socialization and not just for consumption (Ângulo, 2011).…”
Section: Resultsmentioning
confidence: 96%
“…O número de trabalhos voltados para análise de dados de feiras livres que foi identificado é pequeno. Em [Costa et al 2016], por exemplo, o perfil dos consumidores é analisado a partir das respostas dadas a um questionário, sendo os consumidores agrupados, usando K-means [MacQueen 1967], a partir de atributos como idade, escolaridade, profissão, sexo, residência, renda, frequência na feira, dentre outros. Alguns trabalhos focam em determinar razões para escolha de produtos a partir do perfil dos clientes [Silva et al 2016].…”
Section: Análise De Dados Em Feiras Livresunclassified
“…Com relação aos consumidores, estes optam pelas feiras livres em função da proximidade entre estas e suas residências, aliado ao fato de colaborarem para o fortalecimento da economia local. Além disso, os consumidores acreditam que os produtos Research, Society and Development, v. 9, n. 10, e269108312, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8312 14 comercializados nestes locais são mais frescos, baratos e livres de produtos fitossanitários (Costa et al, 2016).…”
Section: Figuraunclassified